2004
DOI: 10.1139/l03-078
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of concrete columns confined by carbon composite tubes

Abstract: The carbon composite tube can play an important role in replacing or complementing longitudinal and transverse reinforcing steels by providing ductility and strength for conventional columns. In this study, both experimental and analytical investigations of axial behavior of large-scale circular and square concrete columns confined by carbon composite tubes are presented. The specimens are filament-wound carbon composite with 90° + 90°, 90° ± 60°, 90° ± 45°, and 90° ± 30° winding angles with respect to a longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…In addition, a group of unbonded-wrapped specimens tested by Harries and Carey [8], Mirmiran et al [9], Mastrapa [10] and Matthys et al [11] were grouped under the category of tube-encased specimens in the database. Furthermore, except for the datasets from Saafi et al [12], Hong and Kim [13] and Ozbakkaloglu and Vincent [14], all the datasets included in the database tables were obtained from specimens that were confined by FRP shells (wraps or tubes) manufactured using a manual hand lay-up technique. The specimens of Ozbakkaloglu and Vincent [14] and Hong and Kim [13], on the other hand, were confined by FRP tubes that were manufactured using an automated filament winding technique; and the specimens of Saafi et al [12] were confined with FRP tubes supplied by a manufacturer, with no specific manufacturing method reported in the source document.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a group of unbonded-wrapped specimens tested by Harries and Carey [8], Mirmiran et al [9], Mastrapa [10] and Matthys et al [11] were grouped under the category of tube-encased specimens in the database. Furthermore, except for the datasets from Saafi et al [12], Hong and Kim [13] and Ozbakkaloglu and Vincent [14], all the datasets included in the database tables were obtained from specimens that were confined by FRP shells (wraps or tubes) manufactured using a manual hand lay-up technique. The specimens of Ozbakkaloglu and Vincent [14] and Hong and Kim [13], on the other hand, were confined by FRP tubes that were manufactured using an automated filament winding technique; and the specimens of Saafi et al [12] were confined with FRP tubes supplied by a manufacturer, with no specific manufacturing method reported in the source document.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, except for the datasets from Saafi et al [12], Hong and Kim [13] and Ozbakkaloglu and Vincent [14], all the datasets included in the database tables were obtained from specimens that were confined by FRP shells (wraps or tubes) manufactured using a manual hand lay-up technique. The specimens of Ozbakkaloglu and Vincent [14] and Hong and Kim [13], on the other hand, were confined by FRP tubes that were manufactured using an automated filament winding technique; and the specimens of Saafi et al [12] were confined with FRP tubes supplied by a manufacturer, with no specific manufacturing method reported in the source document. These datasets are marked with a superscript 'fm' in Table 7 to highlight the fact that the FRP shells of these specimens were manufactured using an automated manufacturing method rather than a manual one.…”
Section: Introductionmentioning
confidence: 99%
“…A number of such studies have been reported in the literature. However, the majority of these studies have been concerned with circular CFFTs (Mastrapa 1997;Saafi et al 1999;Tegola and Manni 1999;Mirmiran et al 2001;Moss 2001;Mandal et al 2005;Zhu et al 2005;Li 2006;Mohamed and Masmoudi 2010;Park et al 2011), and only a few studies have investigated the axial compressive behavior of square and rectangular CFFTs Hong and Kim 2004;Fam et al 2005;Ozbakkaloglu and Oehlers 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, columns in Lillistone and Jolly (1997), Mastrapa (1997), Jolly and Lillistone (1998b), Tegola and Manni (1999) and Hong and Kim (2004) have been disregarded.…”
Section: Selection Criteria Of the Cfft Databasementioning
confidence: 99%
“…It also serves as a formwork and prevents ingress of harmful chlorides and salts, and hence slows down the deterioration in the strength and ductility of concrete columns (Lillistone and Jolly 2000). The influence of different aspects of circular CFFT columns including tube thickness, diameter of the tube, tube height to diameter ratio, unconfined concrete strength, cross sectional shape, orientation of fibres, fibre type, tube manufacturing method, specimen end condition and loading (Axial, flexural and seismic) conditions on the strength and strain enhancement ratios of CFFT columns were investigated by Jolly (1997, 2000), Mastrapa (1997), Jolly and Lillistone (1998a, b), Samaan et al (1998), Matthys et al (1999), Saafi et al (1999), Tegola and Manni (1999), Rizkalla (2001a, b, 2002), Harries and Carey (2002), Hong and Kim (2004), Cole and Fam (2006), Ozbakkaloglu and Saatcioglu (2006), Li and Ou (2007), Mohamed and Masmoudi (2008a, b), Ozbakkaloglu and Oehlers (2008a), Park et al (2011), Ozbakkaloglu (2013a, Ozbakkaloglu and Vincent (2013), Idris and Ozbakkaloglu (2013), Vincent and Ozbakkaloglu (2013a, b), Hadi et al (2015Hadi et al ( , 2016.…”
Section: Introductionmentioning
confidence: 99%